2019
DOI: 10.7547/17-023
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Sociodemographic Characteristics of Patients with Ingrown Nails

Abstract: Background: Ingrown nail is a common health problem that significantly affects daily life due to its painful nature. The purpose of this study was to reveal the clinical and sociodemographic characteristics of ingrown nails. Methods: The clinical and sociodemographic characteristics of patients older than 18 years presenting with ingrown nail were investigated. Results: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 26 publications
0
8
1
Order By: Relevance
“…In a study evaluating 729 ingrown nails, obesity was associated with ingrown nails 39 . We did not find a positive correlation between ingrown toenails and obesity, but two cases of ingrown toenails were found among obese children.…”
Section: Discussioncontrasting
confidence: 76%
“…In a study evaluating 729 ingrown nails, obesity was associated with ingrown nails 39 . We did not find a positive correlation between ingrown toenails and obesity, but two cases of ingrown toenails were found among obese children.…”
Section: Discussioncontrasting
confidence: 76%
“…It has been reported that ingrown toenails are more common in patients who are overweight, lack good foot care, and do not wear appropriate shoes. [3] Our study's patients were normal in weight but lacked good foot care. Our study used the Heifetz classification.…”
Section: Discussionmentioning
confidence: 70%
“…[7,9,19] The popular Winograd technique is frequently reported to carry low recurrence rates; in this approach, the affected nail plate is excised together with the germinal matrix, and the nail tissue is sutured to the digit skin. [3,11] Studies have reported that germinal matrix cauterization (via electrocautery, sodium hydroxide exposure, or dichloracetic acid exposure) in addition to the Winograd technique reduces the recurrence rate of ingrown nails and increases patient satisfaction. [8,9,16] Nail brace application to the nail plate is another treatment option for ingrown nails of different morphologies.…”
Section: ____________________________________________________________...mentioning
confidence: 99%
“…Younger males were probably more likely to be active in sports activities. [10][11][12] A history of matricectomy was reported to be an independent risk factor for recurrence after nail brace treatment. 13 However, in our study, a history of nail surgery was a significant risk factor…”
Section: Discussionmentioning
confidence: 99%